2019
DOI: 10.1111/1759-7714.13248
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of CD34 and SMA in cancer‐associated fibroblasts in stage I–III NSCLC

Abstract: BackgroundEpithelial‐to‐mesenchymal transition (EMT) is a crucial step in lung cancer pathogenesis. Among others, cancer‐associated fibroblasts (CAFs) are reported to regulate this process.ObjectivesTo investigate the prognostic and clinical impact, we analyzed CD34+ and SMA+ CAFs in non‐small cell lung cancer (NSCLC).MethodsRetrospectively, immunohistochemistry was performed to study stromal protein expression of both CD34 and SMA in 304 NSCLC patients with pTNM stage I‐III disease. All tissue samples were em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Notably, the expression of Cd34 by IL17A -/cells only suggested the hematopoietic origin of these fibroblasts, which, however, also expressed higher or similar levels of genes usually associated with a fibroblast phenotype (Acta2, Postn, Pdgfrb, Col1a1, Col5, Col4a1 and Col4a2). Of note, the loss of CD34 on stromal cells has been associated with the increased ability of breast cancer cells to invade surrounding tissues and metastasize (30), and has been defined as an independent prognostic factor in non-small cell lung cancer stage I-III (31). Interestingly, IL17A +/+ CAFs also highly expressed Anxa6 and Areg, which were almost absent in IL17A -/-CAFs.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the expression of Cd34 by IL17A -/cells only suggested the hematopoietic origin of these fibroblasts, which, however, also expressed higher or similar levels of genes usually associated with a fibroblast phenotype (Acta2, Postn, Pdgfrb, Col1a1, Col5, Col4a1 and Col4a2). Of note, the loss of CD34 on stromal cells has been associated with the increased ability of breast cancer cells to invade surrounding tissues and metastasize (30), and has been defined as an independent prognostic factor in non-small cell lung cancer stage I-III (31). Interestingly, IL17A +/+ CAFs also highly expressed Anxa6 and Areg, which were almost absent in IL17A -/-CAFs.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should also cover the co-localization of CD34 with other fibroblastic markers due to fibroblastic heterogeneity [ 52 ], including fibronectin, which promotes the eventual acquisition of a fibrotic response, and TGF β1, which activates the fibroinflammatory genomic program [ 53 , 54 , 55 , 56 ]. Likewise, the investigation of the origin of CAFs from CD34 + SCs/TCs should extend to tumors from other tissue locations (e.g., prostate, lung or skin), for which data that indicate this possibility have been provided [ 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tissue analysis revealed a high mortality rate among 220 patients with NSCLC and high α-SMA expression, indicating that α-SMA is associated with poor survival time ( 56 ). Immunohistochemical analysis of 304 patients with pTNM stage I–III NSCLC revealed that CAF-associated CD34 expression was an independent prognostic factor for stage I–III NSCLC, and that SMA+CAFs were associated with higher tumor stages and promoted tumor progression ( 57 ). The 28 patients with NSCLC were divided into two CAF subgroups, the high desmoplastic CAFs (HD-CAFs) and low desmoplastic CAFs (LD-CAFs), according to the obtained scores and classification based on desmoplasia.…”
Section: Heterogeneity Of Cafsmentioning
confidence: 99%